Levels of acid detergent insoluble protein in grasses and feeds made from them - W. M. Kosolapov; H. K. Khudyakova (Аграрная наука Евро-Северо-Востока, 2021)
The purpose of this research is to assess the level of thermal damage by determining the content of acid detergent insoluble crude protein (ADICP) in perennial cereal forage grasses Bromus inermis, Festuca pratensis, Phleum, depending on the phase of their vegetation (at the beginning of shooting, during the earing and flowering phases), as well as in silage and haylage prepared from them during the same phases. Samples for analyzes were dried at the temperature of 60-65 °C. Nitrogen of ADICP was determined in the residue of ADF (acid detergent fiber) obtained by filtering a solution of acid detergent through a paper filter. With the growth of grasses, an increase in the content of ADF in them was observed, followed by an increase in ADICP in Phleum and especially in Festuca pratensis which was characterized by higher rates of ADF accumulation. In Bromus inermis, the increase in ADF did not lead to an increase in the concentration of ADICP in the grass due to a decrease of its portion in ADF. The content of ADICP in green grass ranged from 0.85 to 1.58 % in dry matter, ADF ‒ from 27.0 to 45.8 %, no correlation was found between them. Conservation of grasses in all phases of their growth caused an increase in the content of ADF compared to the original grass, but the mass fraction of ADICP in the dry matter of silage and haylage was not higher than in the original grass, due to a lower mass fraction of ADICP in the ADF compared to grasses. In this regard, it is noted that if the technology of harvesting silage and haylage is observed, there is no increase in the level of thermal damage to these feeds. In this regard, it is noted, that when the preparation of silage and haylage is carried out according to the required technology, there is no increase in the level of thermal damage to these feeds. There is close correlation between the percentage of ADICP in CP (crude protein) and the contents of CP. The correlation coefficients were -0.83; -0.88 and -0.92 for grasses, silage and haylage, respectively. The lowest percentage of ADICP in CP was observed in the early phases of grass growth. In this regard, there is a need to harvest them in earlier growth phases, since the content of CP decreases with growth and the proportion of indigestible protein in it increases. If there are organoleptic signs of thermal damage to feeds given in the article, it is recommended to make an amendment to CP content on the basis of the result of the analysis for the content of ADICP.